Los Fondos de Inversión en el Perú y el Impuesto a la Renta - Polo Chiroque, Roberto E. (2016)
The investment funds provide an alternative investment mechanism to traditional ones such as banks deposits or the trading of securities, which allows us to obtain profitability as a result of the development of multipleactivities, including commercial ones.Its tax treatment, and particularly in the field of Income Tax, contains severalprovisions that are important to analyze and know in order to understand the tax consequences that generate both for their promoters, for those who administer them and for investors.Being transparent vehicles for tax purposes, the development of its activities at the national level and with the participation of foreign capitals, takes many details that we will explain through this article.